Ouro na terapia anticâncer: compostos organometálicos com ligantes ditiocarbamato e nanopartículas solúveis estabilizadas por carbeno N-heterocíclico - Ana Luiza de Andrade Querino (2023)
The discovery of the medicinal properties of gold compounds has driven the design and synthesis new metallopharmaceuticals for anticancer therapy. The aim of this work was to develop gold(0/I/III) complexes with strategic ligands that can confer greater chemical stability, reactivity, and selectivity to the final compound for effective interaction with biological targets in a physiological environment. Recently, the application of nanotechnology has also proved to be a strategy in nanomedicine to generate drug-delivery systems, diagnostic imaging or even therapy, as demonstrated by gold nanoparticles (AuNPs). The limited chemical stability of gold-based compounds in physiological environments has been a challenge in the discovery of new gold drugs, but organometallic chemistry might overcome this problem. In the first chapter, new organo-gold(III) complexes (C1a - C4a) with the structure [(C^N)AuIII DTC]PF6 were synthesized, with the C^N ligand, 2-anilinopyridine, and dithiocarbamate ligands (DTC = L1 - L4). These ligands consist of L1 ((sodium N-(2,2-dimethoxyethyl)-N-(methyl)- dithiocarbamate, C1a), L2 (sodium 1-piperidinedithiocarbamate, C2a), L3 (sodium 1-piperidine-4-oxo-dithiocarbamate, C3a) and L4 (ammonium 1-pyrrolidinedithiocarbamate, C4a). In addition, the gold(III)-dithiocarbamate coordination analogues (C1b - C4b) with the structure [AuIII(DTC)Cl2] were obtained as potential antitumor drugs. Both series of gold(III) complexes underwent evaluation for their cytotoxic effects on breast tumor cell lines, namely MCF-7 and MDA-MB-231, as well as on healthy breast cells, MCF10a. The IC50 results demonstrated that the synthesized complexes effectively inhibited cell growth. Notably, C3a exhibited a significant antiproliferative effect at sub-micromolar concentrations against MDA-MB-231 cells, displaying moderate selectivity (IC50 = 0.4 µM, IS = 2.0). C3a, as well as its analogous compounds, were selected for further stability studies in solution and reactivity assessments with biomolecules such as N-acetyl-L-cysteine (NAC) and albumin (BSA). The organometallic complex C3a has shown high stability in PBS pH 7.4, whereas C3b, its coordination analog, appeared to undergo hydrolysis reactions. Reactivity studies revealed that C3a, concerning NAC, explore a potential mode of action that involves covalent bonding between the organo-gold(III) fraction and the thiolate, suggesting conversion into a C3a/NAC adduct. In contrast, similar interactions were not observed for C3b and NAC, suggesting that the complex is not reactive under the same conditions. Furthermore, in experiments exploring the possibility of the albumin to act as a drug carrier to its biological targets, C3a has shown a greater ability to suppress the protein fluorescence. The results highlight that the insertion of the C^N ligand to form the organo-gold(III) compounds significantly enhances the stability and reactivity effects of the gold(III)-dithiocarbamate complexes when compared to their coordination analogs, thus underscoring the great potential of organometallic chemistry in the development of novel metallo-drugs for cancer chemotherapy. The second chapter details the synthesis of two novel plasmonic gold nanoparticles, both stabilized by NHC ligands: NHC-COOEt@AuNPs (with NHC-COOEt representing 1,3-diethyl-5-propionyl benzimidazol-2-ylidene) and NHC-COOH@AuNPs (with NHC-COOH denoting 1,3-diethyl-5-carboxylic acid benzimidazol-2-ylidene). These AuNPs underwent comprehensive characterization using UV-vis, infrared, TEM, and TGA spectroscopy. These analyses revealed the presence of the surface plasmon resonance band in both nanoparticles, which exhibited a spherical morphology and an average size of 6 nm. The AuNP functionalized with carboxylic acid is water-soluble and was further characterized using NMR, zeta potential, and assessments of its stability in biologically relevant media. Additionally, the preliminary catalytic potential of NHC-COOH@AuNPs nanoparticles in the 4-nitrophenol reduction reaction in aqueous environments was evaluated. The results indicated that AuNPs exhibit catalytic activity for this reaction, albeit with a moderate rate of substrate conversion. Moreover, preliminary findings suggest that owing to the presence of the carboxylate group in their structure, soluble NHC-COOH@AuNPs nanoparticles can be linked with primary amines through amide coupling reactions. This promising discovery is expected to contribute to research in the functionalization of biomolecules within gold nanoparticles, thereby facilitating the exploration of novel therapeutic strategies involving nanomaterials and the advancement of versatile platforms for various nanotechnology applications.